Negative electron affinity from aluminium on the diamond (1 0 0) surface: a theoretical study. (15th May 2018) - James, Michael C; Croot, Alex; May, Paul W; Allan, Neil L
Abstract: Density functional theory calculations were performed to model the adsorption of up to 1 monolayer (ML) of aluminium on the bare and O-terminated (1 0 0) diamond surface. Large adsorption energies of up to  −6.36 eV per atom are observed for the Al-adsorbed O-terminated diamond surface. Most adsorption sites give a negative electron affinity (NEA), with the largest NEAs  −1.47 eV on the bare surface (1 ML coverage) and  −1.36 eV on the O-terminated surface (0.25 ML coverage). The associated adsorption energies per Al atom for these sites are  −4.11 eV and  −5.24 eV, respectively. Thus, with suitably controlled coverage, Al on diamond shows promise as a thermally-stable surface for electron emission applications.